Does the terrain influence running critical power and biomechanics? An in-field study with highly trained trail runners - Jaén-Carrillo, D.; Ruiz-Alias, S. A.; García-Pinillos, F. (European Journal of Applied Physiology, 2025)
This study aimed to assess the effects of three flat running surfaces (i.e. athletic track, road, and gravel) on the critical power (CP) parameters and running patterns of highly trained trail runners. Within a two-week timeframe, thirteen male and seven female trail runners underwent three testing sessions to evaluate CP and the work over CP (W`). Each session comprised two time trials of 9 and 3 minutes, separated by a 30-min rest, in which a Stryd running power meter was used to collect the data. The CP and W` were subsequently determined using the inverse of time linear CP model. There were no significant differences in CP across the different surfaces (F(2,38)= 1.4; p = 0.253). However, significant differences were found in W` (F(2,38)= 3.8; p = 0.032). Specifically, athletes displayed a higher W` on the track compared to gravel (1.8 [0.2 to 3.4] kJ, p = 0.026), and higher, though non-significant, W` on the road compared to gravel (0.9 [-0.7 to 2.5] kJ, p = 0.478). Regarding the running patterns, the athletes displayed lower duty factor on the track compared to gravel (-1.1 [-2.2 to -0.1] %; p = 0.030) as well as on the road compared to gravel (-1.1 [-2.0 to -0.1] %; p = 0.019). In conclusion, the CP remained stable across surfaces, whereas W` was reduced on gravel compared to track and road. The differences in W` were accompanied by significant changes in the athletes` running patterns. Specifically, athletes exhibited a lower duty factor on the track and road compared to gravel, resulting in a more aerial running form.